GARAP KARAWITAN PAKELIRAN; PAKELIRAN SANDOSA LAKON KEMBANG KUDHUP PUPUS (Perspektif Estetika Pakeliran Nuskma dan Mungguh) - Catur Nugroho; Ananto Sabdo Aji (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2021)
This research discusses the work of karawitan pakeliran in a Pakeliran Sandosa with story Kembang Kudhup Pupus, which is explored through the basic aesthetic perspective of pakeliran, namely the concept of nuksma and respectively. The purpose of this discussion is to understand the extent to which an element of performing karawitan pakeliran can determine the achievement of an aesthetic puppet show. The results of the analysis show that the work of karawitan pakeliran in Pakeliran Sandosa Lakon Kembang Kudhup Pupus can be understood to reach the aesthetic level of pakeliran respectively. This can be seen through the creation of accuracy, harmony, and appropriateness between the composition of the performance karawitan pakeliran including gendhing and tembang to the needs of the events of the play and the inner atmosphere experienced by the puppet. As for the achievement of the aesthetics of pakeliran nuksma which is able to motivate the effect of catharsis for the admirer in the framework of karawitan pakeliran can be felt through the pattern of melody and gendhing songs and songs arranged in such a way; by paying attention to the compatibility between vocal techniques, beats, and musical graphic arrangements that are oriented to the dynamics of the gendhing sense.